A self-tuned rotational vibration energy harvester for self-powered wireless sensing in powertrains. (15th November 2021) - Gunn, B.; Alevras, P.; Flint, J.A.; Fu, H.; Rothberg, S.J.; Theodossiades, S.
Highlights: Novel self-tuning rotational vibration energy harvester concept for powertrains. The concept eliminates the use of protruding beams in rotational vibration energy harvester. Pendulum on tautochrone path for resonance matching a rotational frequency order. The generated power drives an electronic circuit with a temperature sensor. A physical prototype tested at lab validates the proposed design. Abstract: During conversion between mechanical and electrical energy within a machine, or vice-versa, vibrations (or perturbations of the rotational speed) are usually present. These vibrations can be converted into relatively small but useful amounts of electrical energy that can power wireless sensors. In this paper, a novel self-tuning concept of a rotational vibration energy harvester for energy conversion applications is presented. The design concept combines a self-tuned oscillator with an eccentric mass on a "tautochrone" path of motion so that its natural frequency matches a selected order of the rotational speed of a powertrain in order to harness the energy of rotational oscillations. This original vibration energy harvester design (which does not require protruding beams) enables the implementation of the concept for propulsion applications with the appropriate tuning condition. The mathematical modelling of the device and selection of the key design parameters suggest sufficient generated power to successfully drive an electronic circuit equipped with a temperature sensor. A physical prototype is manufactured and experimentally tested, validating the proposed design. The device is demonstrated to be capable of powering a wireless temperature sensor transmitting data every 2 s for a range of more than 1000 rpm of the shaft rotational speed. Higher data transmission rates could be achieved by optimising the design of the harvester, which currently has an overall volume <60 cm 3 .